The European saber-toothed cat (Homotherium latidens) found in the "Spear Horizon" at Schöningen (Germany). Issue 89 (December 2015) - Serangeli, Jordi; Van Kolfschoten, Thijs; Starkovich, Britt M.; Verheijen, Ivo
Abstract: The 300, 000 year old Lower Paleolithic site Schöningen 13 II-4 became world famous with the discovery of the oldest well-preserved and complete wooden spears. Through ongoing excavations, new archaeological discoveries of scientific importance are still being made from the same archaeological layer where the spears were found. In this context, remains of a rare carnivore species, the European saber-toothed cat ( Homotherium latidens ), were recovered. Here we present five teeth and one humerus fragment that are unambiguously from two individual saber-toothed cats. The humerus is a unique specimen; it shows evidence of hominin impacts and use as a percussor. The Homotherium remains from Schöningen are the best documented finds of this species in an archaeological setting and they are amongst the youngest specimens of Homotherium in Europe. The presence of this species as a carnivore competitor would certainly have impacted the lives of late Middle Pleistocene hominins. The discovery illustrates the possible day-to-day challenges that the Schöningen hominins would have faced and suggests that the wooden spears were not necessarily only used for hunting, but possibly also as a weapon for self-defense.